The importance of information localization in scene gist recognition - Loschky, Lester C.; Sethi, Amit; Simons, Daniel J.; Pydimarri, Tejaswi N.; Ochs, Daniel; Corbeille, Jeremy L. (My University, 2007)
People can recognize the meaning or gist of a scene from a single glance, and a few recent studies have begun to examine the sorts of information that contribute to scene gist recognition. We used visual masking coupled with image manipulations (randomizing phase while maintaining the Fourier amplitude spectrum (RISE: Sadr & Sinha, 2004)) to explore whether and when unlocalized Fourier amplitude information contributes to gist perception. In four experiments, we found that differences between scene categories in the Fourier amplitude spectrum are insufficient for gist recognition or gist masking. While the global 1/f spatial frequency amplitude spectra of scenes plays a role in gist masking, local phase information is necessary for gist recognition, and for the strongest gist masking. Moreover, the ability to recognize the gist of a target image was influenced by mask recognizability, suggesting that conceptual masking occurs even at the earliest stages of scene processing.
Keywords: Scene perception; Scene gist; Scene recognition; Scene categorization; Visual masking; Spatial masking